Potential Protective Effect of Zingiber officinale in Comparison to Rosuvastatin on High-fat diet-induced Non-alcoholic Fatty Liver Disease in Rats - Ramadan, Osama Ibrahim; Nasr, Mohamed; El-Hay, Osama M.M. Abd; Hasan, Abdulkarim; Abd-Allah, Ezz-Eldin E.; Mahmoud, Mohammed E.; Abd-Allah, Fatma M.; Abuamara, Tamer M. M.; Hablas, Mohammed G. A.; Awad, Moaaz M. Y.; Diab, Mahmoud; Taha, Ahmed M.; et al. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Non-alcoholic fatty liver disease (NAFLD) is a common liver disease affecting nearly 25% of adults worldwide with related risk factors including obesity, metabolic, and inflammatory diseases. Many therapeutic remedies of natural or synthetic properties were used. AIM: This study aimed to investigate and compare the effects of ginger/rosuvastatin (ROSU) on the liver of rats with induced NAFLD. MATERIALS AND METHODS: Forty adult male albino rats were used in this study and divided into four equal subgroups, Group I, control received the standard rat chow diet and given normal saline (1 ml/kg/day), Group II, high-fat diet (HFD) group, Group III, received HFD+ ROSU (15 mg/kg/day), and Group IV, HFD+ Zingiber officinale (10% W/V) for 6 weeks. At the end of our experiment, the rats were sacrificed then blood samples were collected for biochemical analysis of lipid profiles and liver enzymes, liver specimen was prepared for light and electron microscopic examination, and measurement of tissue level of malondialdehyde. RESULTS: NAFLD caused degenerative changes and lipid deposition in liver cells as evidenced by microscopic results and laboratory tests. Treatment with ginger/ROSU alleviated those changes. CONCLUSION: Ginger and ROSU could ameliorate liver functions in NAFLD and ginger effect is superior to ROSU.